2014
DOI: 10.4103/0019-5545.140640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychiatry training on attitude of medical students toward mental illness and psychiatry

Abstract: Context:Attitude of fresh graduates toward psychiatric patients is important to bridge the treatment gap due to mental illness. Psychiatry as a subject has been neglected in the undergraduates of MBBS.Aims:(1) To compare the attitude of medical students and interns in a medical college toward mental illness and psychiatry. (2) To assess the impact of psychiatric training on attitude toward the mentally ill person and mental illness.Settings and Design:Cross-sectional, single assessment study conducted at a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 13 publications
(37 reference statements)
3
28
1
Order By: Relevance
“…In line with previous research,[ 16 19 ] our study also demonstrated improvement in medical students’ attitude towards people with mental illness in benevolent and stigmatization domains. There were no statistically significant differences were observed in separatism, stereotype, restrictiveness, and pessimistic prediction domains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous research,[ 16 19 ] our study also demonstrated improvement in medical students’ attitude towards people with mental illness in benevolent and stigmatization domains. There were no statistically significant differences were observed in separatism, stereotype, restrictiveness, and pessimistic prediction domains.…”
Section: Discussionsupporting
confidence: 92%
“…Very few studies from India assessed the impact of psychiatric exposure in changing the attitudes of medical students toward people with mental illness. [ 15 16 17 ] It is therefore, the present study was aimed to examine the attitudinal differences between students those have undergone psychiatric training exposure and those who have not, toward people with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in India have shown a remarkably low opinion of psychiatry among medical professionals. Gulati et al (2014) found that medical students and interns in medical schools were discouraged from family members and peers from taking up psychiatry. An astonishing 85% of medical interns in this study believed that a residency in psychiatry is only considered when medical graduates fail to obtain a position in any other specialty.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that psychiatric postings do change some of the attitudes of medical students, though many studies do not replicate this (Gulati, Das and Chavan, 2014,[ 5 ] Konwar, Pardal and Prakash et al ., 2012,[ 8 ] Amini, Moghaddam and Nejatisafa et al . 2013,[ 1 ] Lyons, 2014,[ 10 ] Fischel, Manna and Krivoy et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%